1998
DOI: 10.1046/j.1365-3008.1998.d01-38.x
|View full text |Cite
|
Sign up to set email alerts
|

Ten years of Arabian oryx conservation breeding in Saudi Arabia – achievements and regional perspectives

Abstract: The National Commission for Wildlife Conservation and Development was established in 1986 to oversee all wildlife conservation programmes in Saudi Arabia. The Arabian oryx Oryx leucoryx is one of the flagship species of the Saudi Arabian reintroduction policy. It has been captive‐bred since 1986 at the National Wildlife Research Center near Taif. With the creation of a network of protected areas in the former distribution range of the species, attention has shifted to the release of captive‐bred oryx into Maha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…An endangered species, the Arabian oryx has been the focus of re-introduction projects throughout the Middle East (Stanley Price, 1989;Ostrowski et al, 1998). Formerly, this species was distributed over much of the Arabian peninsula, but now the only viable free-living herds occur in the desert of central Saudi Arabia and the western Rub al-Khali or Empty Quarter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An endangered species, the Arabian oryx has been the focus of re-introduction projects throughout the Middle East (Stanley Price, 1989;Ostrowski et al, 1998). Formerly, this species was distributed over much of the Arabian peninsula, but now the only viable free-living herds occur in the desert of central Saudi Arabia and the western Rub al-Khali or Empty Quarter.…”
Section: Discussionmentioning
confidence: 99%
“…In 1990, Arabian oryx were reintroduced into Mahazat as-Sayd, a large protected area 160·km north-east of Taif, Saudi Arabia. Captive-reared animals survived and reproduced without supplemental food and water; the population has increased significantly over the past decade and now numbers more than 450 individuals (Ostrowski et al, 1998;Treydte et al, 2001). Arabian oryx can live without access to drinking water in arid and hyperarid deserts , including the Rub al-Khali, one of the driest regions in the world (Meigs, 1953).…”
Section: Heterothermy and The Water Economy Of Free-living Arabian Ormentioning
confidence: 99%
“…In 1986, a captive breeding program was launched at National Wildlife Research Center (NWRC) for re-establishing this endangered species in Saudi Arabia. In 1990, a founder population of 17 oryx was released into Mahazat as-Sayd protected area (MSPA) in Saudi Arabia (Ostrowski et al, 1998). From 1990 to 1993, a total of 72 Arabian oryx had been reintroduced into MSPA not only from NWRC but also from many international collections.…”
Section: Introductionmentioning
confidence: 99%
“…However, massive hunting and scarcity of habitat caused extirpation of this antelope from the wild in early 1970s (Henderson, 1974). The foresighted determination and sincere efforts of certain groups saved the last few animals from extinction by nurturing them in captivity and then successfully reintroducing them into the protected areas (Mesochina et al, 2003;Spalton et al, 1999;Ostrowski et al, 1998). Although the savior of Arabian oryx in captivity had become an international symbol of conservation success (Dixon and Jones, 1988) some untoward events in Oman indicated that the reintroduction programs might be prone to partial or total collapse despite their initial success .…”
Section: Introductionmentioning
confidence: 99%